Should the Federal Government Fund Short-Term Postsecondary Certificate Programs? - Sandy Baum; Harry J. Holzer; Grace Luetmer (Institute of Labor Economics (IZA), 2021)
We consider whether the US should extend Pell grant eligibility to short-term certificate programs (i.e., below the current floor of 600 hours). We provide new descriptive evidence on who enrolls in certificate programs, who completes them, how students finance them, who defaults on loans, and on their labor market value. We find that certificate holders earn about 10 percent more than high school graduates and 20 percent more than those with GEDs. The variance in their labor market value across fields is very high. But we find no evidence that certificates above and below the current cutoff generate differing labor market value. Thus, reducing the floor for program eligibility would improve the opportunity of low-income workers to receive effective job training.
Keywords: J24; 330; short-term training; certificates; pell grants; community college